Uterine Artery Embolization for Iatrogenic Uterine Vascular Injuries - S. Vignesh; T. Mukuntharajan; B. Madhumitha; A. K. Kabhilan; M. Sindhu (Journal of Clinical Interventional Radiology ISVIR)
Purpose Uterine curettage or surgery can lead to uterine vascular injuries such as arteriovenous malformations (AVMs) or pseudoaneurysms (PsAs), and patients may present with life-threatening uterine bleeding. The purpose of our study is to evaluate the effectiveness of uterine artery embolization (UAE) in patients with abnormal uterine bleeding due to iatrogenic vascular injuries.